PENGARUH CARA PENGOLAHAN DAN JUMLAH DAUNSIRIH MERAH (Piper crocatum) TERHADAP PERTUMBUHAN Streptococcus mutans (Kajian in vitro) - , DINA PUSPARANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Streptococcus mutans is one of the bacteria that causes dental caries. The proportion of this bacteria is the highest number in humanâs dental plaque. Prevention of plaque formation can be done chemically by mouthwash containing antibacterial compounds. Red betel leaf (Piper crocatum) contains antibacterial phenol compounds that can inhibit the growth of the bacteria. There are two popular method to prepare the mouthwash are boiling and steeping the red betel leaf (Piper crocatum). The aim of this study is to determine the inhibition of Streptococcus mutans bacteria after given the application of boiling water and steeping water of red betel leaf (Piper crocatum) with 10 and 20 pieces of leaves. The red betel leaf was made by boiling and brewing it with the number of 10 and 20 leaves. Streptococcus mutans was used a pure cultures that was diluted by physiological saline to obtain 108CFU/ml value. The effect of treatment group to the growth of Streptococcus mutans could be seen by measuring the optical density (OD) value before and after incubation for 24 hours. The optical density of bacterial growth was measured using spectrophotometer with 600nm wavelength. The results of One Way Anova test showed a significant difference between treatment groups (p <0,05). The smallest growth of Streptococcus mutans was seen in the boiling red betel leaf with 20 pieces of leaves. These results support the hypothesis about the way processing and the number of red betel leaf (Piper crocatum) give affect significantly to the growth of Streptococcus mutans.